Unite: Ames, ISU, student, citizen, + place - Meessmann, Andrew (Kansas State University, 2009)
College districts are unique places that often times blend the culture, history, and the future direction of a city. They are places that foster knowledge, interaction, and diversity. A successful college district enables all citizens to help shape a place that is unique amongst other districts throughout the city. They are places where people relax, work, socialize, think, revolt, and reunite. They are, perhaps, the most important districts within college towns. The intent of this project is to completely reinvent a district to be one that all citizens (permanent and student) of Ames, Iowa can utilize throughout the year. Reversing the negative perceptions of Campustown through design and programming will help recreate a district that fosters interaction among students of Iowa State University and the citizens of Ames. Further, the recreation of Campustown will benefit the community in terms of image, economics, environment, and place. Campustown will no longer be perceived as an enclave of substandard student housing, trashy bars, and a district that caters to only one group. It will be a place where people come together to celebrate Ames and ISU and to come together to meet friends and family. To enable a thorough understanding of successful college districts, two case studies were examined in great detail to help understand what makes these places work. A complete site inventory and analysis of Campustown was also conducted to help determine where and what shortcomings are present throughout the site. Several different programming elements have been selected that would be appropriate to locate in the Campustown area. And finally, a complete master plan has been created that will enable Campustown to function properly long into the future for every citizen of Ames.
Keywords: College district; Ames; Berkeley; Iowa City; Campus town; Pedestrian mall; Architecture (0729); Landscape Architecture (0390); Urban and Regional Planning (0999)